212k views
0 votes
The function g(x) is defined as g(x) = 7x2 + 1. What is g(–2) ?

User Ran Avnon
by
5.0k points

2 Answers

1 vote

Final answer:

To find g(-2), substitute -2 for x in the function g(x) = 7x2 + 1.

Step-by-step explanation:

To find g(-2), we need to substitute -2 for x in the function g(x) = 7x2 + 1.

g(-2) = 7(-2)2 + 1

g(-2) = 7(4) + 1

g(-2) = 28 + 1

g(-2) = 29

Therefore, g(-2) = 29.

User Irudaya Rajasekar
by
5.2k points
0 votes

Answer:

-27

Step-by-step explanation:

7(-2)*2+1 = -27

User Tomasz Plaskota
by
4.4k points